Porous Lactose-Modified Chitosan Scaffold for Liver Tissue Engineering: Influence of Galactose Moieties on Cell Attachment and Mechanical Stability - Birong Wang; Qinggang Hu; Tao Wan; Fengxiao Yang; Le Cui; Shaobo Hu; Bo Gong; Min Li; Qi Chang Zheng (International Journal of Polymer Science)
Galactosylated chitosan (CTS) has been widely applied in liver tissue engineering as scaffold. However, the influence of degree of substitution (DS) of galactose moieties on cell attachment and mechanical stability is not clear. In this study, we synthesized the lactose-modified chitosan (Lact-CTS) with various DS of galactose moieties by Schiff base reaction and reducing action of NaBH4, characterized by FTIR. The DS of Lact-CTS-1, Lact-CTS-2, and Lact-CTS-3 was 19.66%, 48.62%, and 66.21% through the method of potentiometric titration. The cell attachment of hepatocytes on the CTS and Lact-CTS films was enhanced accompanied with the increase of galactose moieties on CTS chain because of the galactose ligand-receptor recognition; however, the mechanical stability of Lact-CTS-3 was reduced contributing to the extravagant hydrophilicity, which was proved using the sessile drop method. Then, the three-dimensional Lact-CTS scaffolds were fabricated by freezing-drying technique. The SEM images revealed the homogeneous pore bearing the favorable connectivity and the pore sizes of scaffolds with majority of 100 μm; however, the extract solution of Lact-CTS-3 scaffold significantly damaged red blood cells by hemolysis assay, indicating that exorbitant DS of Lact-CTS-3 decreased the mechanical stability and increased the toxicity. To sum up, the Lact-CTS-2 with 48.62% of galactose moieties could facilitate the cell attachment and possess great biocompatibility and mechanical stability, indicating that Lact-CTS-2 was a promising material for liver tissue engineering.